2013
DOI: 10.1097/mpa.0b013e3182a6db8e
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perioperative Blood Glucose Levels on Pancreatic Cancer Prognosis and Surgical Outcomes

Abstract: Although diabetes mellitus (DM) and pancreatic cancer (PC) are intricately linked, a comprehensive review addressing the impact of DM on PC prognosis and surgical outcomes is lacking. PubMed search was performed (1980-2012) using keywords "pancreatic cancer", "diabetes mellitus", "glucose intolerance", "pancreatic resection", "prognosis", and "post-operative outcomes". The search results were analyzed to determine the strength of association between DM and PC and to assess the impact of DM on PC prognosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 50 publications
3
31
1
1
Order By: Relevance
“…Pancreatic adenocarcinoma is frequently accompanied by atrophy and duct dilatation distal to the tumor, [26] and duct obstruction can interfere with pancreatic endocrine function and can cause DM. [12,14] There are reports that preoperative DM improved after PD in some patients, [10,12,30] supporting our data that the acute pancreatic duct dilatation caused by obstruction by pancreatic cancer is reversible. Another mechanical change that accompanies is the removal of tumor mass, which can secrete diabetogenic agent.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Pancreatic adenocarcinoma is frequently accompanied by atrophy and duct dilatation distal to the tumor, [26] and duct obstruction can interfere with pancreatic endocrine function and can cause DM. [12,14] There are reports that preoperative DM improved after PD in some patients, [10,12,30] supporting our data that the acute pancreatic duct dilatation caused by obstruction by pancreatic cancer is reversible. Another mechanical change that accompanies is the removal of tumor mass, which can secrete diabetogenic agent.…”
Section: Discussionsupporting
confidence: 77%
“…The causal relationship between pancreatic cancer and DM is unclear, although some evidence indicates DM caused by pancreatic cancer may be reversible after surgical resection. [30] In the present study, the prevalence of preoperative DM in all patients was 53.3%, which was more than twice as higher than values reported on mixed disease entities. [9,10,12] Considering that baseline serum glucose was measured during the immediate preoperative period, it is likely that so-called acute or new-onset DM cases caused by pancreatic cancer, whether by duct obstruction or tumor-related diabetogenic material, were included in the present study.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Numerous studies have shown an association between new-onset non-insulin-dependent diabetes and the development of pancreatic cancer. [7][8][9] Therefore, newonset diabetes in an otherwise fit individual might prompt consideration of early-stage pancreatic cancer. Screening for this disease is generally only recommended for asymptomatic individuals at increased risk.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%